CONCEPTS AND BASIS OF INTERNATIONAL RELATIONS IN ISLAMIC GOVERNMENT PERSPECTIVE - Arifin, Zarul; Saliro, Sri Sudono (Jurnal Syariah, 2021)
After the Muslims spread Islam throughout the universe, the contact of the Muslims with the a‘jam nations had entered a new chapter in international relations. Territorial boundaries displayed in plain sight do not make Muslims limit themselves in interactions between countries. The relationship between Muslims and other nations is inspired by the teachings of Islam itself, which requires Muslims always to maintain peace between Muslims and internal and external Muslims. Islam has laid the foundation of peace in international relations with one main stipulation that Muslims are not allowed even to interfere in the internal affairs of other nations. The methodology used in this research is to use a literature review approach, namely reviewing the literature related to this research. The purpose of this study is to reveal how Islam regulates relations with non-Muslims, both in the territory of Islam and with the region of non-Muslims, as exemplified by the Prophet Muhammad how he established links with the Quraish infidels through the Hudaybiyah agreement and with the other unbelievers such as the agreement contained in the Medina Charter. The results of this study revealed that since the time of the Prophet Muhammad, SAW had taught to have good relations with other nations, and it was passed on by the companions of the Prophet, even regarding today how each country should maintain good relations with other countries and of course it can be profitable for both countries.